[PP.28.13] IS THE SEVERITY OF NOCTURNAL HYPOXEMIA IN PATIENTS WITH OSAS INVOLVED IN INCREASING BLOOD PRESSURE?. (September 2017) - Dediu, G.; Balaceanu, A.; Diaconu, C.; Iancu, A.; Stoica, A.; Aron, G.; Dina, I.
Abstract : Objective: Hypertension is a condition frequently associated with obstructive sleep apnea (OSAS). The most important risk factors for OSAS are obesity and male gender. To assess the association between OSAS and hypertension in a group of patients diagnosed with OSAS by cardiorespiratory polygraphy, and evaluate the relationship between the hypertension severity and nocturnal hypoxemia. Design and method: Observational study that enrolled 49 patients with OSAS, monitored by apnea-hypopnea index (AHI), blood pressure, weight, glycemia and nocturnal hypoxemia.degree Results: The clinical description of the group of study is made in table below: In our study 47, 82% of patients with severe OSAS are hypertensive, 38, 46% of those with moderate OSAS and 40% of those with mild OSAS. In hypertensive patients with OSAS oxyhemoglobin saturation below 90% is found in approximately 11, 68% of sleep duration. The increase of blood pressure concomitantly with nocturnal hypoxemia degree in patients with OSAS was noted. Figure. No caption available. Conclusions: Hypertension is commonly associated with OSAS, a significant number of patients with mild OSAS are hypertensive. There is not a significant difference between the incidence of hypertension in patients with severe OSAS and those with mild OSAS. The degree of nocturnal hypoxemia might be involved in increasing blood pressure.